KRITIK SOSIAL PADA LAGU-LAGU NAVICULA DALAM ALBUM SALTO KAJIAN: SOSIOLOGI SASTRA - Laurensius Hendro Januandi Sani; Henricus Henricus; Indayani Indayani (Universitas PGRI Adi Buana Surabaya, 2018)
His study aimed to describe social problems and forms of social criticism delivery in Navicula songs in the album